Pseudo dynamic seismic response of reinforced concrete frames infilled with non structural brick masonry. - Colangelo, F.
This paper presents pseudo-dynamic test results on the in-plane seismic behaviour of infilled frames. Thirteen single-storey, single-bay, half size scale, reinforced concrete frame specimens, most of which infilled with non-structural masonry made of perforated bricks and cement mortar are tested. The infills are in contact with frames, without any connector; openings are not covered. The frames are different in their strength and details, reinforcement grade and aspect ratio. Seismic input is the 1976 Tolmezzo (Friuli, Italy) ground acceleration, to which specimens are subjected two times : virgin and damaged by the previous test. The global seismic response of initially virgin infilled specimens considerably differs from that of bare specimens. This follows a dramatic change of properties : compared to a bare frame, the initial stiffness increases by one order of magnitude, and the peak strength more than doubles. The peak drift lessens; however, the displacement ductility demand does not. The energy demand is greater. Nevertheless, the influence of infill decreases as damage proceeds. Displacement time histories of damaged specimens are quite similar. at the local level, infill causes asymmetry and concentration of the frame deformation.
Keywords: Infilled frame; Reinforced concrete frame; Masonry infill; Pseudo-dynamic test; Seismic response